ASSESSING GENETIC DIVERSITY AMONG GOSSYPIUM ARBOREUM L. GENOTYPES USING ISSR MARKERS - KHUSHBOO SETHI,; PRIYANKA SIWACH,; SURENDER KUMAR VERMA,; MEGHA SIHAG, (International Journal of Pharma and Bio Sciences, 2015)
The diploid cultivated cotton (Gossypium arboreum) is an invaluable genetic resource for the improvement of primary cotton. First step for this is a systematic race wise characterization using molecular markers. Present study attempted to characterize 95 genotypes with ISSR markers. The 100 selected markers produced a total of 397 bands, of which 368 were polymorphic. The PIC values ranged from 0.23 to 0.5 (average 0.40). Resolving power and marker index were calculated to know the efficiency of markers. The mean number of effective alleles was 1.409 and the mean value of shannon’s information index was 0.368. AMOVA test showed that 17% of molecular variance were due to 6 population groups and rest due to variance in each group. The six populations were distributed in two major clusters by UPGMA while PCoA analysis could not differentiate population groups accurately. Outcomes of this research will help in identification of right genotypes for any given breeding program.